2002
DOI: 10.1530/eje.0.1470655
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of iodide uptake by human chorionic gonadotropin in FRTL-5 cells: effects on sodium/iodide symporter gene and protein expression

Abstract: Background: Various clinical and experimental findings support the concept that human chorionic gonadotropin (hCG) can stimulate iodide uptake in thyroid cells. Design: We investigated the molecular mechanisms underlying the effects of hCG on iodide uptake, and particularly its action on the expression of Na þ =I 2 symporter (NIS) mRNA and protein. Methods: Iodide uptake was analyzed in FTRL-5 cells by measuring 125 I concentrations in cells after a 30-min exposure to 0.1 mCi carrier-free Na 125 I in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…hCG upregulates NIS expression in thyroid cells and placental cell lines (4,5,31,33). To examine whether the decrease of NIS expression in low O 2 levels could be contributed to by low hCG levels, we examined hCG mRNA expression and protein secretion in the same samples used for NIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hCG upregulates NIS expression in thyroid cells and placental cell lines (4,5,31,33). To examine whether the decrease of NIS expression in low O 2 levels could be contributed to by low hCG levels, we examined hCG mRNA expression and protein secretion in the same samples used for NIS.…”
Section: Discussionmentioning
confidence: 99%
“…Pendrin is an anion exchanger (37,50,53,55) and is activated by high concentrations of intracellular iodide (63). The pituitary glycoprotein TSH upregulates NIS expression and iodide uptake (5,29), whereas iodide has the opposite effect (15). In placenta, materno-fetal transfer of iodide involves iodide uptake through the apical trophoblast cell membrane and efflux through the basal cell membrane.…”
mentioning
confidence: 99%
“…TSH stimulates the NIS promoter and NIS upstream enhancer (NUE; , Ohmori et al 1998, Ohno et al 1999, Taki et al 2002, increases the half-life of the NIS protein, and stimulates the trafficking of the NIS to the plasma membrane (Riedel et al 2001). Direct stimulation of the TSH receptor in Graves' disease by antibody (Saito et al 1997, Caillou et al 1998, Castro et al 1999, Lazar et al 1999, constitutive activating mutations of the TSH receptor in a hyperfunctioning thyroid adenoma (Mian et al 2001), or the weak agonist human chorionic gonadotropin (hCG; Hershman 1999, Arturi et al 2002, activate the cAMP pathway and result in marked NIS expression. In contrast, the expression of AIT is not increased in hyperfunctioning thyroid adenomas or Graves' disease (Lacroix et al 2004, Porra et al 2005.…”
Section: Tsh Regulation Of Nis and Other Iodide Transporters In Normamentioning
confidence: 99%
“…In the present study, we found that NIS gene expression is downregulated by ATDs. Genetic factors, such as the proximal promoters including thyroid transcription factor 1 (TTF1), NIS TSH-responsive factor 1 (NTF1) or NIS upstream enhancers, iodine, cytokines and anti-NIS antibody, are known to regulate NIS gene expression [21][22][23]. These factors may also have influenced NIS expression in the present study.…”
Section: Discussionmentioning
confidence: 72%